2020
DOI: 10.1073/pnas.1916716117
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid phase separation of type II diabetes-associated IAPP initiates hydrogelation and aggregation

Abstract: Amyloidoses (misfolded polypeptide accumulation) are among the most debilitating diseases our aging societies face. Amyloidogenesis can be catalyzed by hydrophobic–hydrophilic interfaces (e.g., air–water interface in vitro [AWI]). We recently demonstrated hydrogelation of the amyloidogenic type II diabetes-associated islet amyloid polypeptide (IAPP), a hydrophobic–hydrophilic interface-dependent process with complex kinetics. We demonstrate that human IAPP undergoes AWI-catalyzed liquid–liquid phase separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 41 publications
2
81
0
Order By: Relevance
“…Given sufficient time, the large droplets could potentially undergo subsequent maturation through a sol-gel transition. 20, 45–54…”
Section: Resultsmentioning
confidence: 99%
“…Given sufficient time, the large droplets could potentially undergo subsequent maturation through a sol-gel transition. 20, 45–54…”
Section: Resultsmentioning
confidence: 99%
“…Other amyloid-associated proteins also undergo phase separation, at least in vitro (Elbaum-Garfinkle, 2019). For example, liquid-liquid phase separation of IAPP is catalyzed by the air-water-interface (Pytowski et al, 2020). Interestingly, Comparison with the non-fibrillogenic rat IAPP revealed that phase separation does not require the presence of the highly amyloidogenic region (residue 20-29), but hydrogelation and aggregation do (Pytowski et al, 2020).…”
Section: Roles Of Flanking Regions In Protein Functionmentioning
confidence: 99%
“…For example, liquid-liquid phase separation of IAPP is catalyzed by the air-water-interface (Pytowski et al, 2020). Interestingly, Comparison with the non-fibrillogenic rat IAPP revealed that phase separation does not require the presence of the highly amyloidogenic region (residue 20-29), but hydrogelation and aggregation do (Pytowski et al, 2020). The prion-like functional amyloid Sup35 also undergoes phase separation, generating protein-specific environmental responses.…”
Section: Roles Of Flanking Regions In Protein Functionmentioning
confidence: 99%
“…Given sufficient time, the large droplets could potentially undergo subsequent maturation through a sol-gel transition. 20,[44][45][46][47][48][49][50][51][52][53] To probe the jamming dynamics of RNAs inside large droplets, we calculated the MSDs for each nucleotide in the RNA chain (Fig. 6c).…”
Section: Monomer Dynamics Inside the Condensates Is Sluggish: Evidencmentioning
confidence: 99%